2014
DOI: 10.1103/physrevc.89.015805
|View full text |Cite
|
Sign up to set email alerts
|

Hadronic and hybrid stars subject to density-dependent magnetic fields

Abstract: In the light of the very massive neutron stars recently detected and the new possible constraints for the radii of these compact objects, we revisit some equations of state obtained for hadronic and hybrid stars under the influence of strong magnetic fields. We present our results for hadronic matter taking into account the effects of the inclusion of anomalous magnetic moment. Additionally, the case of hybrid stars under the influence of strong magnetic fields is considered. We study the structure of hybrid s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 74 publications
3
82
0
Order By: Relevance
“…[32] and widely adopted in subsequent works [21][22][23][33][34][35][36][37][38][39][40][41]. This ansatz, however, violates Maxwell equations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[32] and widely adopted in subsequent works [21][22][23][33][34][35][36][37][38][39][40][41]. This ansatz, however, violates Maxwell equations.…”
mentioning
confidence: 99%
“…While some of the first works advocated that the pressure, having in mind the thermodynamical pressure obtained from the thermodynamical potential that relates pressure to density, should be isotropic [20][21][22][23], based on an interpretation given in Ref. [24], other works were based on the fact that the energy-momentum tensor gives different contributions for the parallel and perpendicular pressure [25][26][27][28] (see Ref.…”
mentioning
confidence: 99%
“…Over the years, it has been shown that the presence of strong magnetic fields significantly affects the energy levels of charged particles due to Landau quantization. These effects have been taken into account in the EoS of models in order to describe hyperon stars (Chakrabarty et al 1997;Broderick et al 2000Broderick et al , 2002Lopes & Menezes 2012;Sinha et al 2013;Casali et al 2014;Gomes et al 2014;Gao et al 2015), quark stars (Perez Martinez et al 2008;Felipe et al 2011;Orsaria et al 2011;Paulucci et al 2011;Denke & Pinto 2013;Dexheimer et al 2014;Isayev 2015), hybrid stars (Rabhi et al 2009;Dexheimer et al 2012Dexheimer et al , 2013, and stars with meson condensates Schramm et al (2015). The effects of the anomalous magnetic moment (AMM) were also investigated through the corresponding coupling of the baryons to the electromagnetic field tensor (see Canuto & Chiu 1968a;Broderick et al 2000Broderick et al , 2002Strickland et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that strong magnetic fields populate the vast majority of the astrophysical compact objects and that they can significantly affect several properties of the star have served as motivation for many works focused on the study of the EoS of magnetized neutron stars, without considering , or considering the magnetic-field interaction with the particle anomalous-magnetic-moment [88,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113]. An important characteristic is that the EoS in a uniform magnetic field becomes anisotropic, with different pressures along the field and transverse to it [73,94,98].…”
Section: Introductionmentioning
confidence: 99%